Make America Great Again in Science: A Guide for All Sovereign Nations - Herndon, J. Marvin (Advances in Social Sciences Research Journal, 2020)
U. S. President Donald J. Trump is leading America and the world against the elitist-globalist goal of a One World Government. His efforts to free American entrepreneurs from unwarranted control by others are producing an economic renaissance. From a lifetime of first-hand knowledge and experience, I describe the problems that beset American science, and posit solutions for producing the cutting-edge science that Trump’s economic renaissance requires.